THE EFFECT OF GUIDED INQUIRY LEARNING MODEL TOWARDS STUDENTS SCINCE PROCESS SKILLS ABOUT ELASTICITY TOPIC IN CLASS XI MAWARIDUSSALAM A.Y 2019/2020 - Rizqi Afnan; Derlina Nasution (INPAFI (Inovasi Pembelajaran Fisika), 2020)
The objective to be achieved through this research ate to find out the significant effect of guided inquiry learning model on science process skills students in the Elasticity Topic in Class XI Islamic Boarding School MAWARIDUSSALAM A.Y 2019/2020. This type of research is a class experiment with the design of two groups prestest-postest. The population in this study were all students of class XI IPA semester I at Islamic Boarding School MAWARIDUSSLAM. Sampling was done by cluster random sampling. Class XI IPA 1 as an experimental class aplied by KPS and class XI IPA 2 as a control class applied to conventional learning, amounting to 24 and 18 respectively. The Science Process Skill Instrument consist of 8 essays. Before learning a pretest is conducted to see the students’ initial abilities in both classes. The average value of the Science Process Skill pretest in the experimental class was 13.54 and the control class was 14.12. Based on the t-test the initial ability of students in both classess is the same Science Process Skills. The average posttest score for Science Process Skills in the experimental class was 36.63 and the control class was 19.44. Based on the monova test there are significantdifferences, which means there is an influence of the guided inquiry learning model on Science Process Skills in students.Keywords: Science Process Skilss And Guided Inquiry